Template synthesis and characterization of nanostructured lithium insertion electrodes and nanogold/porous aluminum oxide composite membranes - Patrissi, Charles J., author; Martin, Charles R., advisor (Colorado State University. Libraries, 2000)
A membrane-based template synthesis method was used to prepare nanostructured Li-ion battery electrodes and nanogold/porous aluminum oxide composite membranes. Membrane-based template synthesis is a general method for the preparation of nanomaterials which entails deposition of the material of interest, or a suitable precursor, within the nanometer-diameter pores in a porous template membrane. This method allows for control of nanoparticle size and shape and is compatible with many methods of synthesis for bulk materials. The template membranes used in this work were commercially available porous polycarbonate filtration membranes and nanoporous aluminum oxide membranes that were prepared in-house. Nanostructured electrodes of orthorhombic V2O5, prepared using membrane-based template synthesis, were used to investigate the effects of Li-ion diffusion distance and V2O5 surface area on electrode rate capability. Nanowires of V2O5 were prepared by depositing a precursor in the pores of microporous polycarbonate filtration membranes. The result was an ensemble of 115 nm diameter, 2 μm long nanowires of V2O5 which protruded from a V2O5 surface layer like the bristles of a brush. The Li* storage capacity of the nanostructured electrode was compared to a thin film control electrode at high discharge rates. Results show that the nanostructured electrode delivered three to four times the capacity of the thin film electrode at discharge rates above 500C. A membrane based template synthesis method was also used to prepare crystalline V2O5 electrodes which have high volumetric charge capacities, at high discharge rates, compared to a thin-film control electrode. In order to obtain high volumetric rate capability, the as-received polycarbonate template membranes were chemically etched to increase membrane porosity. Nanofibrous electrodes of crystalline V2O5 were then prepared by depositing an alkoxide precursor in the pores of the etched membranes. Electrode volumetric capacity was further increased by addition of the V2O5 precursor to the parent nanostructured electrodes. Results on the volumetric and geometric rate capabilities and the cycling performance of these electrodes are presented. Finally, nanogold was electrochemically deposited in porous aluminum oxide template membranes to study the effect of temperature on the shape and optical properties of the gold nanoparticles. Low aspect ratio nanoparticles were observed, via electron microscopy, to be thin skinned, flakes of Au within the pores. After heat treatment at temperatures well below the melting point of gold (< 400 C) these particles changed shape to become nearly spherical. Visually, the color of these membranes changed from blue to red after the heat treatment. in contrast, the nanoparticles with an aspect ratio of ca. 3 showed essentially no detectable change in shape or optical properties after exposure to the same heating program. The membranes started red and did not change color with heating.
Keywords: analytical chemistry; electrical engineering; energy